2016
DOI: 10.18632/oncotarget.8418
|View full text |Cite
|
Sign up to set email alerts
|

A high-content EMT screen identifies multiple receptor tyrosine kinase inhibitors with activity on TGFβ receptor

Abstract: An epithelial to mesenchymal transition (EMT) enables epithelial tumor cells to break out of the primary tumor mass and to metastasize. Understanding the molecular mechanisms driving EMT in more detail will provide important tools to interfere with the metastatic process. To identify pharmacological modulators and druggable targets of EMT, we have established a novel multi-parameter, high-content, microscopy-based assay and screened chemical compounds with activities against known targets. Out of 3423 compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 65 publications
4
15
0
Order By: Relevance
“…EMT is mediated by the binding of various stimuli, such as TGFβ, to specific receptors, which initiates intracellular signaling that regulates the transcription of genes involved in cell-cell adhesion, reorganization of the cytoskeleton, and survival mechanisms to support metastasis (Heerboth et al, 2015;Lotz-Jenne et al, 2016). However, our results suggest that distinct signaling pathways are used for EMT in CAMSAP3-deficient and TGF-β-treated cells.…”
Section: Camsap2 Expression Level Did Not Change In Correlation Withmentioning
confidence: 67%
“…EMT is mediated by the binding of various stimuli, such as TGFβ, to specific receptors, which initiates intracellular signaling that regulates the transcription of genes involved in cell-cell adhesion, reorganization of the cytoskeleton, and survival mechanisms to support metastasis (Heerboth et al, 2015;Lotz-Jenne et al, 2016). However, our results suggest that distinct signaling pathways are used for EMT in CAMSAP3-deficient and TGF-β-treated cells.…”
Section: Camsap2 Expression Level Did Not Change In Correlation Withmentioning
confidence: 67%
“…1b ). Subsequently, mesenchymal cell characteristics were monitored by high-content fluorescence microscopy analysis and quantified, including the deposition of the extracellular matrix protein fibronectin and the formation of focal adhesions and of actin stress fibres 23 . Nine out of 32 differentially expressed miRNAs were able to block or at least delay the EMT process: miR-125b-5p, miR-181b-2-3p, miR-1247-3p, miR-200a-3p, miR-200b-3p, miR-429-3p, miR-1199-5p, miR-145a-3p and miR-504-5p.…”
Section: Resultsmentioning
confidence: 99%
“…The general setup of the screen has been described recently 23 . In brief, NMuMG/E9 cells were plated as duplicates in a 96-well plate and reverse transfected with 20 nM pre-miR miRNA precursors (Ambion; Supplementary Table 4 ) using Lipofectamine RNAiMax (Invitrogen) 2 days prior to the addition of TGFβ for 4 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RhoA, an important member of the Rho family, regulates numerous downstream genes, alters actin structure and morphology and regulates cell proliferation, apoptosis, metastasis and other biological processes (38). A recent study demonstrated that ROCK, an important RhoA regulator, is associated with cell apoptosis, EMT, migration and metastasis (39). In the present study, it was revealed that knockdown of URG11 suppresses TGF-β-induced RhoA and ROCK1 expression levels, indicating that URG11 regulates BPH progression via the RhoA/ROCK1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%